P0511ENHANCER AND SUPER-ENHANCER DYNAMICS IN REPAIR AFTER ISCHEMIC ACUTE KIDNEY INJURY. (6th June 2020) - Wilflingseder, Julia; Willi, Michaela; Lee, Hye Kyung; Olauson, Hannes; Jankowsky, Jakub; Ichimura, Takaharu; Erben, Reinhold; Valerius, M Todd; Hennighausen, Lothar; Bonventre, Joseph Vincent
Abstract: Background and Aims: The endogenous repair process of the mammalian kidney allows rapid recovery after acute kidney injury (AKI) through robust proliferation of tubular epithelial cells. There is currently limited understanding of which transcriptional regulators activate these repair programs and how transcriptional dysregulation leads to maladaptive repair. Here we investigate the existence of enhancer dynamics in the regenerating mouse kidney. Method: RNA-seq and ChIP-seq (H3K27ac, H3K4m3, BRD4, POL2 and selected transcription factors) were performed on samples from repairing kidney cortex 2 days after ischemia/reperfusion injury (IRI) to identify activated genes, transcription factors, enhancer and super-enhancers associated with kidney repair. Further we investigated the role of super-enhancer activation in kidney repair through pharmacological BET inhibition using the small molecule JQ1 in vitro and in acute kidney injury models in vivo. Results: Response to kidney injury leads to genome-wide alteration in enhancer repertoire in-vivo. We identified 16, 781 enhancer sites (H3K27ac and BRD4 positive, H3K4me3 negative binding) active in SHAM and IRI samples; 6, 512 lost and 9, 774 gained after IRI. The lost and gained enhancer sites can be annotated to 62% and 63% of down- and up-regulated transcripts at day 2 after kidney injury, respectively. Super-enhancer analysis revealed 164 lost and 216 gained super-enhancer sites at IRI day 2. 385 super-enhancers maintain activity before and after injury. ChIP-seq profiles of selected transcription factors based on motif analysis show specific binding at corresponding enhancer sites. We observed lost enhancer binding of HNF4A and GR mainly at kidney related enhancer elements. In contrast, STAT3 showed increased binding at injury induces enhancer elements. No dynamic was observed for STAT5. Both transcription factor groups show corresponding mRNA changes after injury. Pharmacological inhibition of enhancer and super-enhancer activity by BRD4 inhibition (JQ1: 50mg/kg/day) before IRI leads to suppression of 40% of injury-induced transcripts associated with cell cycle regulation and significantly increased mortality between days 2 and 3 after AKI. Conclusion: This is the first demonstration of enhancer and super-enhancer function in the repairing kidney. In addition, our data call attention to potential caveats for use of small molecule inhibitors of BET proteins that are currently being tested in clinical trials in cancer patients who are at risk for AKI. Our analyses of enhancer dynamics after kidney injury in vivo have the potential to identify new targets for therapeutic intervention.